Studying the possibility of using PV Solar software system to choose the appropriate panels: Mini Review - Fatima Tariq Ahmed; Hazim H. Hussain; Naseer K. Kasim (African Journal of Advanced Pure and Applied Sciences, 2022)
In recent, the world has seen a shift toward alternative energy, which was chosen for a variety of reasons, including economic feasibility, environmental output, operational cost, and processing unit independence. Alternative or clean energy is divided into several categories, some of which are generated by solar cells and others by fans. In this study, we examined one of these types by investigating the possibility of selecting the appropriate solar cells through the use of a simulation software system for reality (climatic and spatial conditions).